Primary School Students and Teachers' Appreciation of Gregorian Singing - Blašković, Jelena; Prša, Tihomir (Revija za elementarno izobraževanje, 2022)
The aim of this study was to examine the attitudes of primary school students and teachers towards Gregorian singing. The research was conducted during the academic year 2019/2020 and included 381 students and thirty-five primary school teachers in Croatia. The results of the t-test showed a statistically significant high appreciation of Gregorian singing among students and teachers. Using the Kruskal Wallis test, we established that younger student showed greater appreciation compared to older students. Students and teachers expressed positive attitudes towards the examples of Gregorian singing to which they listened. Most subjects indicated that they liked Gregorian singing and desired to get to know it more deeply during music lessons in primary education.
Keywords: Gregorian singing, music lessons, music preferences, primary education